ANALISIS SISTEM PERKAWINAN MERBAU (Intsia bijuga O. Ktze) DI PAPUA BERDASARKAN PENANDA ISOENZIM - Mahfudz Mahfudz; Mohammad Na'iem; Sumardi Sumardi; E B Hardiyanto (Jurnal Pemuliaan Tanaman Hutan, 2010)
Merbau (Intsia bijuga O. Ktze) is an important species to supply wood in Indonesia. Mating system on natural population of merbau can influence genetic diversity of merbau. The objectives of this study were to investigate mating system on natural forest of merbau in Papua. The research used 200 samples of merbau from 10 mother trees in Gunung Meja Forest Research Manokwari-Papua. Isoenzyme analysis was done using four enzyme systems i. e. Peroxidase (POD), Esterase (EST), Glutamate Oxaloacetate Transaminase (GOT) dan Diaphorase (DIA). Data were analysed using MLTR program. The result showed that average genetic diversity (He) 0.463 and total heterozygosity (HT) 0.496. The multilocus population outcrossing rate (tm) and singlelocus population outcrossing rate (ts) were tm = 1.00 and ts = 0.992. Probability of inbreeding rate (tm  - ts) = 0.008.